Exploration and Quality Assessment of Local Trichoderma spp. from the Rhizosphere of Bamboo (Gigantochloa apus) Against Fusarium Wilt Disease in Tomato Plants - Pulle, Yosevin H.; Tanjung, Rosye H.R.; Lantang , Daniel (Jurnal Biologi Papua, 2025)
This study aims to explore and test the quality of Trichoderma spp. local from the rhizosphere of apus bamboo (Gigantochloa apus) against Fusarium spp. wilt disease both in vitro and in vivo in tomato. This research was conducted in the Keerom area, Jayapura, which is one of the centers of food crop production and horticulture in Papua. The data obtained from this study were analyzed by comparing the inhibition of three Trichoderma spp. isolates (Trichoderma sp. 1 isolate, Trichoderma sp. 2 isolate, and Trichoderma sp.3 isolate) against Fusarium spp. The results of the antagonist test showed that the isolate of Trichoderma sp.3 had the highest inhibition (80.56%) against Fusarium spp., followed by Trichoderma sp.2 (66.84%) and Trichoderma sp.1 (27,62%). The implication of this study is that Trichoderma sp. 3 has high potential as an APH in the control of Fusarium spp. wilt disease in tomato plants. The use of Trichoderma spp.-based APH can be an effective and environmentally friendly alternative in reducing the use of chemical pesticides and maintaining the balance of the agro-environmental ecosystem.